Consistent Thermal Conductivities of Spring-Like Structured Polydimethylsiloxane Composites under Large Deformation - Guo, Yongqiang (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.